1993
DOI: 10.1007/bf02542582
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting the shelf stability of sunflower nuts

Abstract: 493DehuUed, raw, whole sunflower kernels of high-oleic acid (HOA) and high-linoleic acid (HLA) types were shelf~table at 23 and 37°C for over one year. Dry-roasted HOA kernels were more stable than dry-roasted HLA kernels. Oilroasted HLA kernels were more stable than dry-roasted ones. Stability of roasting oil and storage temperature had no appreciable effect on shelf stability of kernels.KEY WORDS: Antioxidant, dry mast, high linoleic acid, high oleic acid, oil roast, peroxide value, shelf stability, sunflowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 5 publications
0
11
0
Order By: Relevance
“…The ratio of 18:1 to 18:2 for the sunflower kernels (0.52) was higher than the 0.25 of Robertson et al (1988) sample, the 0.20 of Budin and Breene (1993) sample and the average value for commercial sunflower oil (19/68 ϭ 0.27). The amount of frying oil in the oil roasted sunflower kernels could be estimated from the fatty acid profiles.…”
Section: Results and Discussion Composition Of Sunflower Kernelsmentioning
confidence: 56%
See 2 more Smart Citations
“…The ratio of 18:1 to 18:2 for the sunflower kernels (0.52) was higher than the 0.25 of Robertson et al (1988) sample, the 0.20 of Budin and Breene (1993) sample and the average value for commercial sunflower oil (19/68 ϭ 0.27). The amount of frying oil in the oil roasted sunflower kernels could be estimated from the fatty acid profiles.…”
Section: Results and Discussion Composition Of Sunflower Kernelsmentioning
confidence: 56%
“…Robertson et al (1988) reported 15% frying oil absorption for HLA kernels and 10% for HOA kernels. The same calculation on data from Budin and Breene (1993), showed 8% frying oil absorption for their oil roasted sunflower kernels. From available data, it appears that the amount of frying oil in the oil roasted kernels was proportional to the moisture of the raw kernels.…”
Section: Results and Discussion Composition Of Sunflower Kernelsmentioning
confidence: 71%
See 1 more Smart Citation
“…Published information already describes the effects of harvesting on the content of components, nutrients or antioxidants [13,14] or the oxidative changes of seeds during storage [15,16]. So far no published data are available on the reduction of shelf life and therefore the loss in quality of the seeds and their oils in relation to their damage during harvesting.…”
Section: Resultsmentioning
confidence: 97%
“…Public reaction usually occurs only when rancid or oily flavors lower the quality of food purchased. Different authors studied the changes in fatty acid and tocopherol composition, stability, effect of packaging materials and chemical quality indexes of oils during storage (Fourie and Basson, 1989;Gómez-Alonso et al, 2004;Evans et al, 1973;Okogeri and Margari, 2002;Van der Merwe et al, 2003;Budin and Breene, 1993;Gutierrez and Fernanz, 2002) Especially in countries with high temperatures and limited facilities for cool storage the oxidative deterioration of fats and oils is a great problem. In this case the availability of fats and oils with a high oxidative stability during long term storage under the extreme climatic conditions of these countries is important.…”
mentioning
confidence: 99%